Maintaining physical activity in people with long-term conditions following engagement in physical activity referral schemes: barriers, enablers, and intervention strategies - James P. Gavin (International Journal of Behavioral Nutrition and Physical Activity, 2025)
Abstract Background There is currently limited evidence on the long-term effectiveness of referral programs from healthcare to community sectors to help people with long-term conditions (LTCs) maintain physical activity. This study aimed to (i) identify the support needs of people with LTCs in maintaining physical activity following physical activity referral schemes (PARS); (ii) understand healthcare professionals’ experiences of referring and delivering on PARS, and; (iii) begin co-designing a pathway integrating healthcare, leisure and community to maintain physical activity for LTCs. Methods A qualitative design involved (i) stakeholder mapping, ii) interviews with people with LTCs (n = 15) and healthcare professionals (n = 9), and; (iii) workshops with participants with LTCs (n = 6) and multi-sectoral professionals (n = 15). Workshops involved multi-sectoral professionals responsible for designing, delivering, referring and/or commissioning PARS across health, leisure and community sectors. Interviews and workshops were thematically analyzed, with themes mapped to the Capability, Opportunity, Motivation–Behavior (COM-B) model. Results Participants with LTCs recognized that although PARS increased their psychological and physical capabilities, aging and symptoms impacted their day-to-day capabilities and motivation. Professional feedback and monitoring, complemented by peer support, were essential in mitigating this and maintaining physical activity behaviors. Healthcare professionals were challenged by the time taken to identify community-based opportunities, navigating referrals, and lacked sufficient feedback on client progress, but felt group activities, enjoyment and social support were integral. Workshops highlighted the need for an integrated pathway from medical intervention to community-based support, to improve physical activity maintenance for LTCs. Better partnership working between multi-sectoral agencies was prioritized to increase scheme accessibility, including simple, standardized referrals. Using behavior change techniques to personalize support was also valued, including ‘healthy conversations’ training for healthcare professionals. Conclusions Healthcare, leisure, and community sectors should collaborate to create accessible local activities that promote social support, feedback and monitoring, and public partnership. Healthcare professionals should consider individual capabilities, foster motivation during and after PARS, and facilitate networks for resources and knowledge sharing.